The big book of sides : more than 450 recipes for the best vegetables, grains, salads, breads, sauces, and more - Rodgers, Rick, 1953- (Ballantine Books, 2014)
"Whether planning a quick dinner after work or a holiday meal for a crowd, you will never be stumped for a side dish again. Side dishes make the meal. Rodgers has carefully compiled a variety of wonderful options, from traditional to inspired, Americana to ethnic, Southern fare to California cuisine. Rodgers also shares recipes for relishes, chutneys, pickles, baked goods (from biscuits to foccacia), and even sauces. The book also contains helpful tips on how to stock your pantry, easy-to-follow cooking techniques, gorgeous color photos, and main dish pairing suggestions."--